Openness Muhammadiyah to Women Leader in Amal Usaha Muhammadiyah Kota Pekalongan - Leni Susanti; Panca Kurniati; Alfa Yuliana Dewi (SENTRALISASI, 2022)
Muhammadiyah as harokah manages about being allowed for a woman to participate in organizational activities. At present, many women can lead well. This research conducted to find out how much Muhammadiyah's openness towards the acceptance of women as leaders at Muhammadiyah Charity Foundation owned by Muhammadiyah in Pekalongan. This research is a descriptive quantitative research that is an approach to test objective theory by examining the relationship between variables that describe the response and level of acceptance of Muhammadiyah to female leaders in AUM Pekalongan. Respondents in this study were 24 AUMs in Pekalongan with total sampling or census techniques because of all existing samples were used. The analytical tool is Import Performance Analysis. This research found that women leaders should be concerned in quadrant II. It means that the approaches have been used optimally by leaders to lead their employees or subordinates to achieve the organization’s goals.